2018
DOI: 10.1126/science.aat2058
|View full text |Cite
|
Sign up to set email alerts
|

Lectins modulate the microbiota of social amoebae

Abstract: The social amoeba maintains a microbiome during multicellular development; bacteria are carried in migrating slugs and as endosymbionts within amoebae and spores. Bacterial carriage and endosymbiosis are induced by the secreted lectin discoidin I that binds bacteria, protects them from extracellular killing, and alters their retention within amoebae. This altered handling of bacteria also occurs with bacteria coated by plant lectins and leads to DNA transfer from bacteria to amoebae. Thus, lectins alter the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…We do not know how these Burkholderia confer secondary carriage. Increased lectin expression by D. discoideum farmers has been implicated as the mechanism mediating bacterial food carriage and the addition of exogenous lectin to nonfarmers induces food bacterial retention in amoebae cells and sori (Dinh, Farinholt, Hirose, Zhuchenko, & Kuspa, 2018). It is possible that Burkholderia some strains that may be better symbionts than others, and there is variation among these strains in the proportion of spore population infected.…”
Section: Discussionmentioning
confidence: 99%
“…We do not know how these Burkholderia confer secondary carriage. Increased lectin expression by D. discoideum farmers has been implicated as the mechanism mediating bacterial food carriage and the addition of exogenous lectin to nonfarmers induces food bacterial retention in amoebae cells and sori (Dinh, Farinholt, Hirose, Zhuchenko, & Kuspa, 2018). It is possible that Burkholderia some strains that may be better symbionts than others, and there is variation among these strains in the proportion of spore population infected.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies involving knockout mutants, unbiased mutational screens, genome-wide transcriptional changes and proteomic analysis during phagocytosis, macropinocytosis or infection have produced a large wealth of data, which have been the subject of several reviews in the last years (Bozzaro and Eichinger, 2011;Dunn et al, 2018;Cardenal-Muñoz et al, 2018;Swart et al, 2018). Among more recent data not yet covered by reviews, it is worth mentioning: (I) evidence that Dictyostelium cells are highly sensitive to bacterial chemoattractants, but phagocytosis per se is independent of chemoreceptor sensing (Meena and Kimmel, 2017); (II) in apparent contrast to this, the characterization of the G protein-coupled, folic acid receptor fAR1, which recognizes the saccharide core of LPS and stimulates gram-negative bacterial phagocytosis, providing a plausible mechanism for the involvement of G proteins in phagocytosis ; discrepancy between both results may be due to the different phagocytosis assays used; (III) evidence that Dictyostelium discriminates between Gram-(-) and Gram-(+) bacteria, migrating preferentially toward Gram-(-) bacteria (Rashidi and Ostrowski, 2019), and that their growth on Gram-(-) or Gram-(+) bacteria elicit different transcriptomic profiles, with some genes essential for growth (Nasser et al, 2013); ((IV) the identification of PIKFyve/FAB1 in controlling acidification of phagosomes (Buckley et al, 2019), thus extending previous studies on the role of phosphoinositides in phagocytosis, macropinocytosis and resistance to pathogens (Swart et al, 2018;Hoeller et al, 2013;Peracino et al, 2010; (V) Similarly, it has been shown that the RasGAP IqgC is a negative regulator of macropinocytosis and large particle phagocytosis (Marinović et al, 2019), strengthening the role of Ras signalling in these processes Junemann et al, 2016;Bolourani et al, 2010; (VI) While bacterial phagocytosis is essential for growth, it has also been shown that during slug stage, cells maintain as endosymbionts bacteria that have been coated with the secreted lectin discoidin I, and that could possibly be used later as a food source (Dinh et al, 2018).…”
Section: Biological Processmentioning
confidence: 98%
“…Most recent reviews or relevant papers Cytoskeleton, motility and chemotaxis Gräf et al 2015;Rivero and Xiong, 2016;Stuelten et al 2018;Liu et al 2018;van Haastert et al 2018;Edwards et al 2018;Kriebel et al 2018;Nichols et al 2019;Miyanaga et al, 2018 Phagocytosis, macropinocytosis and endo-lysosomal traffic Williams and Kay, 2018;Williams et al 2019;Pan et al 2018;Meena and Kimmel, 2017;Buckley et al, 20192019;Dunn et al 2018;Dinh et al 2018;Marinović et al, 2019 Cytokinesis Srivastava et al, 2016 Cell adhesion Fujimori et al 2019;Lampert et al 2017 Autophagy Mesquita et al 2017;Fischer et al 2019 Development, pattern formation Yamada and Schaap, 2019 Social evolution Ostrowski, 2019 Dictyostelium as model organism 325…”
Section: Biological Processmentioning
confidence: 99%
“…While the farmer phenotype can be induced in naïve D. discoideum by the mere coculture with Bulkholderia, wild-isolates of D. discoideum have been shown to develop permanent adaptations to tolerate this endosymbiont (Shu et al, 2018). Although the precise mechanisms that enable permissibility to Bulkholderia are not know, the farmer phenotype has been associated to an increased secretion of extracellular lectins by D. discoideum, that may protect the bacteria or induce their tolerance (Dinh et al, 2018;DiSalvo et al, 2015;Shu et al, 2018).…”
Section: Emergence Of Innate Immunitymentioning
confidence: 99%